The Flow-Clutch Scale: Development and preliminary validation in sport and exercise. (January 2022) - Swann, Christian; Driscoll, Janelle; Goddard, Scott G.; Willis, Royce; Schweickle, Matthew J.; Fernandes Ribeiro, Ingrid Araujo; Gatt, Matthew; Jackman, Patricia C.; Vella, Stewart A.
Abstract: Objectives: The Integrated Model of Flow and Clutch States describes two overlapping psychological states that underlie exceptional performance and rewarding exercise experiences. However, research based on this model is currently hampered because no validated measure has yet been developed. Therefore, the aim of this multi-study paper was to develop and provide preliminary validation of the Flow-Clutch Scale in sport and exercise. Design: Using two independent adult samples ( n = 280; n = 264), three studies were conducted to develop and establish preliminary validity of the Flow-Clutch Scale. Method: In Study 1, we developed an initial version of the scale and established content validity using an expert panel. In Study 2, we employed exploratory factor analysis to: identify the most appropriate factor structure; examine the scale's internal consistency; test whether the scale differentiated between individuals who experience flow, clutch, or neither state; and examine relationships with the Flow State Scale-2. In Study 3, we aimed to replicate findings of Study 2 with an independent sample, and employed confirmatory factor analysis to confirm the factor structure, internal consistency, and relationships with the Flow State Scale-2. Results: The results provide preliminary validation of the four-factor, 22-item Flow-Clutch Scale. Conclusions: These studies indicate the Flow-Clutch Scale represents a useful scale for researchers interested in examining flow and/or clutch states in sport and exercise. Recommendations are provided for further research to continue testing, and accumulating evidence for, the validity and reliability of the Flow-Clutch Scale. Highlights: We aimed to develop and provide preliminary validation of the Flow Clutch Scale. In Study 1 an expert panel confirmed content validity of an initial version of the scale. Study 2 refined the measure to 22 items and identified a four-factor structure. Study 3 confirmed the factor structure in an independent sample. These studies provide preliminary evidence of the validity of the Flow Clutch Scale.